ANALYTICAL HIERARCHY PROCESS APPROACH ON CONSUMER PREFERENCES IN SUPERMARKET SELECTION FRESHMART, MULTIMART AND HYPERMART - Purnomo, Kharies Dwi Manossoh (Universitas Sam Ratulangi, 2014)
Consumer play an important role in modern retail business. Without consumer, the modern retail business canâ€™t survive. The individual consumer has their own set of preferences and determination of these is based upon culture, education, and individual tastes. Supermarket must identify what consumer want because in Manado consumer face a lot of choice in selecting supermarket. This research purpose is to analyzed factor that influence consumer preferences in supermarket selection, identify which supermarket people choose the most and each supermarket key strength.This research used the Analythical Hierarchy Process (AHP) in processing the data. Population in this research is people in Manado who has experience in shopping at Freshmart, Multimart, and Hypermart. The sample of this research is 50 respondents of simple random sampling. The result have shown the most criterion that influence consumer when selecting the supermarket is product quality and brand image is the least criterion that influence consumer when selecting supermarket. Freshmart become the most preffered supermarket chosen by consumer. Location, product quality, and product variety are the key strength of each supermarket. Finally, every supermarket in Manado must give more attention to product quality, location and price as the most influence criteria when people decide to shop at supermarket. Â Keywords : consumer preferences, supermarket selection